The Antihyperlipidaemic Property of Methanol Leaf Extract of Chrysophyllum albidum in Albino Rats (Wistar Strain) Fed on High Fat Diet. - Ojemekele, Osebhahiemen Happiness; Omoregie, Ehimwenma Sheena (JOURNAL OF ADVANCES IN BIOLOGY, 2018)
Hyperlipidaemia is a well documented risk factor for cardiovascular disease, a major cause of mortality world-wide. Chrysophyllum albidum (white star apple) has several medicinal properties. Ingestion of the fruits has been found to lower lipid levels in the body, due to its high fibre content. Research works have shown that several parts of the plant are highly medicinal. The aim of this study was to evaluate the antihyperlipidaemic property of methanol leaf extract of Chrysophyllum albidum in Wistar rats fed with a high fat diet. Thirty male Wistar rats weighing between 130g-150g were distributed into five groups of six animals each. Group 1 received normal fat diet (NFD). Group 2 received high fat diet (HFD; Grower mash supplemented with 20% beef tallow). Group 3 received HFD and a standard lipid lowering drug, orlistat (20mg/kg body weight, p.o). Animals in group 4 and 5 were fed on HFD and received methanol leaf extract of Chrysophyllum albidum, 250mg/kg and 500mg/kg, p.o respectively. The administration was carried out for 56 days. On the 57th day, animals were sacrificed by cervical dislocation. Organs were harvested and blood samples were collected for biochemical analyses. Results showed that the administration of HFD increased the total cholesterol, LDL-Cholesterol, triglycerides levels and decreased the HDL- cholesterol levels significantly (p <0.05). Simultaneous administration of Chrysophyllum albidum extract significantly (p<0.05) reduced the total cholesterol, LDL-Cholesterol, triglycerides levels and increased HDL- Cholesterol. Final body weights of animals that received Chrysophyllum albidum extract were significantly (p<0.05) lower than final body weights of animals in groups 2 (negative control). Results from Histopathology revealed inflammation of the liver and kidney of rats in group 2 (negative control). On the other hand, rats that received orlistat and Chrysophyllum albidum extract had normal liver and kidney architecture. It was concluded that Chrysophyllum albidum extract showed antihyperlipidemic effect in rats fed with beef tallow supplemented diet.